TRAINING AND COUNSELING ON DISINFECTION DURING REPAIR OF ACRYLIC RESIN DENTURES AT DENTAL LABORATORIES IN SURABAYA AND JEMBER - Dwiyanti Feriana Ratwita; Okti Setyowati; Endang Kusdarjanti (Darmabakti Cendekia: Journal of Community Service and Engagements, 2019)
Background: The dentist who handles a broken acrylic resin denture base case will send the denture to be repaired by a dental technician in the dental laboratory. The transfer of work is likely to pose a risk of cross-infection (for example AIDS, hepatitis, tuberculosis, pneumonia, and herpes. Purpose: To transfer science and technology based on community needs objectively to get a strong foundation in implementing health management for dental technicians. Methods: Training on how to use disinfection materials as well as participatory counseling using slides through LCD projectors, and using props along with interactive discussions and also mentoring when trainees take disinfection measures. Results: The implementation includes 3 activities, that is counseling, training and monitoring Counseling is carried out by providing knowledge about how to disinfect dentures, then training in how to do disinfection, the way is to train dental technicians to disinfect using chlorhexidine by spraying on the denture surface, then monitored. Conclusion: So far the dental laboratory has not carried out any disinfection at the time of denture repair. With counseling and training in this community partnership program, dental technicians know the importance of disinfection denture to prevent cross infection, so that it will then do it.